2019
DOI: 10.1186/s12889-019-7134-1
|View full text |Cite
|
Sign up to set email alerts
|

HPV vaccination has not increased sexual activity or accelerated sexual debut in a college-aged cohort of men and women

Abstract: Background The human papillomavirus (HPV) is the most common sexually transmitted infection and is linked to several types of cancer. HPV vaccination uptake in the U.S. is relatively low, despite the vaccine’s high efficacy. Some parents of adolescents have concerns that vaccination will encourage sexual behavior and therefore choose not to vaccinate. Previous studies investigating vaccination and sexual behavior have included only young women and girls. Methods The obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 30 publications
3
28
1
Order By: Relevance
“…For example, community-based studies evaluating risky sexual behaviour among young adults who were vaccinated against human papillomavirus showed they engaged in less risky behaviours such as being less likely to not use a condom and drink two or more times per week. 16 In our study, we found that PPE use (while not significant) was lower for firefighters who tested positive versus those who tested COVID-19 antibody negative (85.7% vs 94.2%)-more than a twofold difference. A recent systematic review examining clustering and co-occurrence of multiple risk behaviours (ie, drinking, physical activity, diet and so on) found the strongest associations by occupation (up to fourfold increased odds) and by educational attainment.…”
Section: Discussioncontrasting
confidence: 47%
“…For example, community-based studies evaluating risky sexual behaviour among young adults who were vaccinated against human papillomavirus showed they engaged in less risky behaviours such as being less likely to not use a condom and drink two or more times per week. 16 In our study, we found that PPE use (while not significant) was lower for firefighters who tested positive versus those who tested COVID-19 antibody negative (85.7% vs 94.2%)-more than a twofold difference. A recent systematic review examining clustering and co-occurrence of multiple risk behaviours (ie, drinking, physical activity, diet and so on) found the strongest associations by occupation (up to fourfold increased odds) and by educational attainment.…”
Section: Discussioncontrasting
confidence: 47%
“…A physician's recommendation for the HPV vaccine has been shown to promote uptake and acceptance of HPV vaccination. 36 Therefore, physicians can be an important target to promote HPV vaccination and alleviate concerns about its link to sexual activity which is widely disproven [29][30][31][32] .…”
Section: Inclination Towards Sexual Activitymentioning
confidence: 99%
“…Such arguments are commonly used against other public health interventions such as HPV vaccination-that vaccination will encourage promiscuity. Yet there is no evidence this is the case (24).…”
mentioning
confidence: 98%